PENGARUH PENGGUNAAN PERMAINAN SCRABBLE DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN - Nur Alim Amri (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
The problem in this research is how to use scrabble game in improving early childhood reading ability in group B of TK Nurul Taqwa Gowa. This study aims to determine the description of the early reading ability of children before and after the application of scrabble games and to determine the effect of scrabble games in improving early childhood reading abilities. Type of research is an experimental study with pre-experimental designs using the one group pretest-posttest design consisting of pretest, treatment, and posttest. Subjects were 15 children in group B1. The results showed that the average score in the pretest was 8.93 and at the posttest the average value was 19. Then it was also supported by the results of calculations using the wilcoxon signed rank test. In the SPSS program, the Asymp sig (2-tailed) value was obtained. of 0.001 here the probability is below 0.05 or p <0.05, which means that H0 is rejected. So, it can be concluded that there is an effect of using scrabble game in improving reading ability.